Demonstration of nonvolatile multilevel memory in ambipolar carbon nanotube thin-film transistors. (26th May 2015) - Li, Guanhong; Li, Qunqing; Jin, Yuanhao; Qian, Qingkai; Zhao, Yudan; Xiao, Xiaoyang; Wang, Jiaping; Jiang, Kaili; Fan, Shoushan
Abstract: Multilevel memories have attracted significant interest because of their larger memory density per unit cell. Here, we investigated multilevel operation with ambipolar carbon nanotube thin-film transistors. Three distinct conduction states and a direct change between any of them were demonstrated by selecting appropriate values for the magnitude and duration of each program/erase voltage pulse. A low operation voltage of 5 V and a short duration of 1 s were obtained by utilizing a bilayer Al2 O3 -epoxy dielectric to enhance the gate modulation efficiency. A tradeoff exists between low-voltage operation and fast switching for a given device.